Paediatric selective IgM deficiency and IgG4 deficiency: an extremely unusual association. (1st September 2014) - Bolia, Rishi; Misra, Durga Prasanna; Aggarwal, Amita; Srivastava, Anshu
Abstract : Humoral immunodeficiency disorders present in children after 6 months of age with recurrent respiratory and gastrointestinal infections. These may be due to the absence of B cells causing panhypogammaglobulinaemia, or due to selective deficiencies in immunoglobulin subfractions. We present the case of a child with selective deficiency of IgM and IgG4 resulting in chronic diarrhoea and recurrent lower respiratory infections. With appropriate treatment of infections, the child had good symptom relief. Such an unusual combination of antibody deficiency has not been previously described in children. This case serves to illustrate the need for awareness to institute timely therapy for infection along with appropriate prophylactic measures like vaccination for these children.